The 5′ NAD cap of RNAIII modulates toxin production in staphylococcus aureus isolates - Morales-Filloy, Hector Gabriel; Zhang, Yaqing; Nübel, Gabriele; George, Shilpa Elizabeth; Korn, Natalya; Wolz, Christiane; Jäschke, Andres (Journal of bacteriology, 2020)
Nicotinamide adenosine dinucleotide (NAD) has been found to be covalently attached to the 5′ ends of specific RNAs in many different organisms, but the physiological consequences of this modification are largely unknown. Here, we report the occurrence of several NAD-RNAs in the opportunistic pathogen Staphylococcus aureus. Most prominently, RNAIII, a central quorum-sensing regulator of this bacterium’s physiology, was found to be 5′ NAD capped in a range from 10 to 35%. NAD incorporation efficiency into RNAIII was found to depend in vivo on the −1 position of the P3 promoter. An increase in RNAIII’s NAD content led to a decreased expression of alpha- and delta-toxins, resulting in reduced cytotoxicity of the modified strains. These effects seem to be caused neither by changes in RNAIII’s secondary structure nor by a different translatability upon NAD attachment, as indicated by unaltered patterns in in vitro chemical probing and toeprinting experiments. Even though we did not observe any effect of this modification on RNAIII’s secondary structure or translatability in vitro, additional unidentified factors might account for the modulation of exotoxins in vivo. Ultimately, the study constitutes a step forward in the discovery of new roles of the NAD molecule in bacteria. - IMPORTANCE Numerous organisms, including bacteria, are endowed with a 5′ NAD cap in specific RNAs. While the presence of the 5′ NAD cap modulates the stability of the modified RNA species, a significant biological function and phenotype have not been assigned so far. Here, we show the presence of a 5′ NAD cap in RNAIII from S. aureus, a dual-function regulatory RNA involved in quorum-sensing processes and regulation of virulence factor expression. We also demonstrate that altering the natural NAD modification ratio of RNAIII leads to a decrease in exotoxin production, thereby modulating the bacterium’s virulence. Our work unveils a new layer of regulation of RNAIII and the agr system that might be linked to the redox state of the NAD molecule in the cell.
Gesehen am 15.04.2020